Assessment of the influence of façade location and orientation in indoor environment of double-skin building envelopes with perforated metal sheets. (October 2019) - Blanco, J.M.; Buruaga, A.; Cuadrado, J.; Zapico, A.
Abstract: Double-skin perforated sheet façades, enclosures consisting of perforated screens, air chambers and glass/wall sheets, are features of modern building design that are winning greater acceptance. A detailed analysis of their suitability across Europe is first performed here. A reference building both with and without the protective double-skin perforated sheet envelope is subjected to a comparative test of solar energy gains with regard to the environment. Additionally, the results of a preliminary survey are presented on the visual perceptions of different patterns of perforated metal sheets. Then the behaviour of these configurations is addressed, through a complete "Energyplus® model" (design builder). A test campaign on a reference perforated screen mounted on a service building of reference was fully monitored over one year, supported by thermographic data recorded for additional validation purposes during the same period. The new parametric energy assessment takes additional variables into account, such as orientation and location of the façade, demonstrating that the real performance for such enclosures greatly depends on them. Accordingly, the influence of different combinations of perforated screens on cooling, heating and lighting loads demonstrates the suitability of a previously optimized configuration in terms of relative energy savings. Highlights: Suitability demonstrated of perforated metal sheets at different places. New parametric energy assessment evaluates façade orientation and latitude. Energy savings and design optimization of enclosures in Spain addressed.